Professional identity and representations of the organization’s values - A socio-organizational approach to the system of identity action - benbouzid, khaled; belhemari , bachir (Social Sciences Journal)
This article aims to address the issue of professional identity and the mechanisms of its construction and formation within the heart of work organizations. This topic has become one of the most discussed subjects in the field of sociology in general and the sociology of organizations in particular, due to its importance and impact on individuals and actors within the organization, considering the individual as a being who influences and is influenced through social relationships and interaction with others, according to what is imposed by the work culture in the organizational environment. This contributes to building individuals and influencing their individual and collective behavior. Through the work field or organizational socialization, the individual recognizes and evaluates the self and acquires a professional identity that adds to the trajectory of their previously acquired identity from primary socialization. According to sociologists, identity is not given in one go; it is a long and complex process, and the individual does not build it alone but relies on others. The self is a mirror of society, and organizations are merely a reflection of society in a more rational and organized manner. Thus, professional identity is a reproduction of social identity through self-construction and behavior modification within the organizational system.